2016
DOI: 10.1002/cmdc.201500531
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Affinity by Correct Ligand Preorganization for the S2 Pocket of Thrombin: A Study by Isothermal Titration Calorimetry, Molecular Dynamics, and High‐Resolution Crystal Structures

Abstract: Structural preorganization to fix bioactive conformations at protein binding sites is a popular strategy to enhance binding affinity during late-stage optimization. The rationale for this enhancement relates to entropic advantages assigned to rigidified versus flexible ligands. We analyzed a narrow series of peptidomimetics binding to thrombin. The individual ligands exhibit at P2 a conformationally flexible glycine, more restricted alanine, N-methylglycine, N-methylhomoalanine, and largely rigidified proline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…The result showed that S49 could bind to thrombin via H-bond interaction with Asp189, Ser214, Gly216 and Gly219 (Fig. 2), which was consistent with previous studies16. The low root mean-square deviation (RMSD) of the re-docked and co-crystallized conformation of S49 was calculated to be 1.48 Å (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The result showed that S49 could bind to thrombin via H-bond interaction with Asp189, Ser214, Gly216 and Gly219 (Fig. 2), which was consistent with previous studies16. The low root mean-square deviation (RMSD) of the re-docked and co-crystallized conformation of S49 was calculated to be 1.48 Å (Fig.…”
Section: Resultssupporting
confidence: 89%
“…The X-ray crystal structure of thrombin (PDB code: 4UFD. Resolution: 1.43 Å) resolved recently was designated to be the docking template35. Crystallographic water molecules in the structure were deleted and hydrogen atoms were added.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, only combining the complex structures with the thermodynamic data, can we understand the underlying mechanism of affinity changes resulting from the variation of protein–ligand interactions and establish a rational and validated SAR. Together with the protein–ligand complex structures, the thermodynamic profiling of ligand binding not only serves as an important indicator for hit or lead selection, but also interprets the nature of protein–ligand recognition and provides invaluable information for further optimization ( Ruhmann et al, 2016 ).…”
Section: Thermodynamic Characterization Of Ligand–target Bindingmentioning
confidence: 99%
“…7 Gerhard Klebe's group modified former thrombin inhibitors and calculated the binding free energy of each complex by the isothermal titration calorimetry (ITC) method to develop new thrombin inhibitors. 8,9 In their study, two groups of systems were combined with the same thrombin (Figure 1A) and different ligands (Figure 1B,C). In one group, the P3 side chain of ligand S28 (Figure 1B) was gradually modified to form four new ligands, namely, S29, S54, TIF, and S00.…”
Section: Introductionmentioning
confidence: 99%
“…This previously reported research showed that the binding free energy is significantly strengthened in the final modified ligands. 8,9 Exploring the reasons for the enhancement of binding free energy caused by the ligand modification can provide effective guidance for drug design. Therefore, to explore the different binding mechanisms of the thrombin−ligand systems, the two above-mentioned groups are used to conduct specific research in our work.…”
Section: Introductionmentioning
confidence: 99%